Treatment Of Zakat Accounting At The National Zakat Amil Body (Baznas) In Bantaeng Regency - Dangkeng, Arianto; Ramli, Muh. (Universitas Muhammadiyah Makassar, 2022)
The Treatment of Zakat Accounting at the National Zakat Agency (BAZNAS) in Bantaeng Regency. The aims of this study was to determine whether the zakat accounting treatment at the National Zakat Agency (BAZNAS) in Bantaeng Regency was in accordance with Islamic Financial Accounting Standards by analyzing financial reports from BAZNAS Banteng Regency was then analyzed whether it was in accordance with PSAK Sharia No. 109 of 2020 which applies today. Data collection methods used in this study were interviews, observation, and documentation. The analytical method used is descriptive analysis. Based on the analysis results obtained financial statements BAZNAS Bantaeng Regency shows in the practice of collecting and distributing zakat, infaq and alms funds still use the single entry method is very simple and easy to understand. In the bookkeeping there are only financial reports in the form of changes in the funds of zakat, infaq and alms. Thus, BAZNAS Bantaeng Regency has not implemented the recording, measurement, disclosure in accordance with the accounting standards that set out in PSAK Sharia No. 109 of 2020